Effect of chiral silver nanoparticles on prolyl-oligopeptidase binding and activity - Batista, Carin C. S.; Toledo, Victor H.; Ramos, Marcos P. C.; Oliveira, Vitor; Acuña, Javier; Icimoto, Marcelo Y.; Nantes, Iseli L. (Frontiers in Nanotechnology, 2024)
Introduction: Silver nanoparticles have a diversity of applications both in biological and technological areas. More recently, studies conducted in the Nano/Bio interface have demonstrated that chiral nanocrystals grew in chiral templates, and nanostructures functionalized with chiral molecules present specific properties. These properties apply to advanced materials, energy, medicine, and pharmacology. Methodology: The present study synthesized silver nanoparticles on silver seeds using D- and L-histidine as templates and borohydride as a reducing agent. Results and Discussion: The nanoparticles were characterized by UV-visible spectroscopy and presented surface plasmon resonance (SPR) bands around 415 nm. CD spectra showed signals in the region of the SPR band, indicating the growth of nanocrystals with chiral distortion. Synthesized silver nanoparticles were also characterized by high-resolution transmission electron microscopy (HRTEM), which evidenced the presence of histidine corona. The silver nanoparticles were functionalized with prolyl-oligopeptidase (POP), a prolinespecific endopeptidase expressed in the brain. This enzyme cleaves neuroactive peptides involved in memory, learning, and neurodegeneration. The enzyme POP was expressed with a His-tag to provide competitive binding affinity to silver nanoparticles covered by D- and L-histidine. Considering the biological importance, POP was chosen as a model for studying the functionalization of chiral silver nanoparticles regarding the chiral discrimination for binding affinity and stabilization.